POTRET MASYARAKAT URBAN DALAM NOVEL METROPOP CRITICAL ELEVEN KARYA IKA NATASSA - Wanda, Winia; Hayati, Yenni; Nst., M. Ismail (Jurnal Bahasa dan Sastra, 2018)
This article portrays the culture of entertainment, consumerism, pragmatism, secularism or profane lifestyle, hedonism, taste uniformity and instant culture in Ika Natassa's Critical Eleven metropop novel. The research is qualitative research and using descriptive method.Â  Based on the results of data analysis found the portrait of urban communities in the novel metropop Critical Eleven as follows. First, entertainment culture, such as music, traveling to places of interest, shopping, sports, partying and more browsing the internet and chatting with friends through social media. Secondly, the culture of consumerism, such as buying expensive goods for toys and collectibles, the use of well-known brands as their fashion, "hunting" food in famous restaurants and shopping, and for the particular needs of urban societies more attentive to the quality and costliness of goods. Third, pragmatism, society becomes antifondationalist, antirepresentationalist, and antirealist. Fourth, secular or profane lifestyle, religion is not so important in today's life. Fifth, hedonis, like living full of entertainment, royal or consumptive, and make fashion as a self-image. Sixth, the uniformity of the sense, that makes the community no longer have a distinctive culture. Seventh, instant culture, teaches that life needs a process to achieve success.Keywords: urban community, metropop novel, literature